Abordagem triangular: uma experiência estética na educação infantil - Pereira, Elenice de Fátima (2021)
The present work, enrolled in the research line School Practices and Application of Knowledge of the Postgraduate Program in Teaching in Basic Education (PPGEEB), from the Center for Teaching and Research Applied to Education (CEPAE), at the Federal University of Goiás - UFG, arises from my research entitled: “Triangular Approach: an aesthetic experience in Early Childhood Education”. It intends to reflect about the use of Ana Mae Barbosa's Triangular Approach with children from three to four years old, since this proposal by Barbosa has not been used in Early Childhood Education in the city of Goiânia. It is justified by the importance of working with Visual Arts in a contemporary, progressive, and dialogical way, and by the need to seek interactive and meaningful alternatives in the school environment with children in this age group that can contribute to their development. The goal of this research is to understand how the three dimensions of Barbosa's Triangular Approach can contribute to perception, sensitivity, intuition, curiosity, and creative imagination, considering the several possibilities of expression and manifestation through the artist's historical contextualization, the image reading of a work, and also, through his drawing. It seeks to provide children with aesthetic experiences beyond those that are part of their routine, beyond immediate reality, seeking new ways to learn and teach Art. This research had as main theoretical references, Barbosa (2007, 2012, 2014), Iavelberg (2013) Vygotsky (2018). In the scope of action research, allied to qualitative research, an art project was developed using the Triangular Approach with twenty children from Grouping D-2 1, during six months, at CMEI Cristiano Emídio Martins, in the city of Goiânia. In the art project, I followed all the impressions, gestures, manifestations, expressions of the children about getting to know the artist, about reading the image of the artist's work, and also, the drawing produced by them. As an educational product, presents the title “Visual Arts with the Triangular Approach: ways and possibilities"-, a digital portfolio was built containing photos, videos, drawings, and speeches of the children with all the experiences lived in the art project. In this case, the pedagogical interventions worked with Barbosa's Triangular Approach showed that it is possible to develop with children in this age group, a deeper and contextualized artistic work.